Investigation of SPAD values ​​and morphometric characteristics of leaves in wild blackberry populations on Stara Planina - Jovana (Acta herbologica, 2021)
In the paper examines ecophysiological and ecomorphological parameters in Rubus hirtus Waldst. & Kit. from three natural populations from Stara Planina. The content of total chlorophyll in leaves, estimated by the SPAD method, as well as leaf width and leaf width / length ratio had the highest values ​​in population A, which inhabits a forest community dominated by hornbeam and sessile oak and grows in vegetative shade. Smaller values ​​of the examined parameters were observed in populations B (which is also located within the forest complex), and C (which is located in a relatively open habitat). Inter-population differences in the examined parameters can be partially interpreted as adaptation to light conditions of habitats (significant differences between individuals from populations A and C), while the values ​​of parameters in population B cannot be explained by light conditions but indicate the need to consider complex environmental conditions factors at that site, primarily contamination of soil and groundwater with heavy metals.
Keywords: Rubus hirtus, natural populations, chlorophyll, leaf morphometry, Stara planina